An Integrated Model for Simulating Regional Water Resources Based on Total Evapotranspiration Control Approach - Jianhua Wang; Xuefeng Sang; Zhengli Zhai; Yang Liu; Zuhao Zhou (Advances in Meteorology)
Total evapotranspiration and water consumption (ET) control is considered an efficient method for water management. In this study, we developed a water allocation and simulation (WAS) model, which can simulate the water cycle and output different ET values for natural and artificial water use, such as crop evapotranspiration, grass evapotranspiration, forest evapotranspiration, living water consumption, and industry water consumption. In the calibration and validation periods, a “piece-by-piece” approach was used to evaluate the model from runoff to ET data, including the remote sensing ET data and regional measured ET data, which differ from the data from the traditional hydrology method. We applied the model to Tianjin City, China. The Nash-Sutcliffe efficiency (Ens) of the runoff simulation was 0.82, and its regression coefficient R2 was 0.92. The Nash-Sutcliffe Efficiency (Ens) of regional total ET simulation was 0.93, and its regression coefficient R2 was 0.98. These results demonstrate that ET of irrigation lands is the dominant part, which accounts for 53% of the total ET. The latter is also a priority in ET control for water management.